Sulfan - další plynný hormon? - Stárka, Luboslav (Chemické listy, 2009)
Hydrogen sulfide is an important signalling biological compound of endogenous origin. It is produced in mammalian tissues by enzymes ß-synthase and cystathionine ?-lyase especially from cysteine and homocysteine. H2S plays important roles under physiological and pathophysiological conditions in the central nervous and cardiovascular systems, in smooth muscles and other organs.
Keywords: metabolismus; Muscles; hormony; cystathionin-beta-synthasa; Cystathionine beta-Synthase; Inflammation; Cardiovascular System; sulfan; plyny; zánět; Hydrogen Sulfide; Hormones; Cystathionine gamma-Lyase; Gases; lidé; svaly; cystathionin-gama-lyasa; Humans; centrální nervový systém; Financing, Organized; Metabolism; Central Nervous System; kardiovaskulární systém; financování organizované